The Rationale for Initiation and Continuation of Drug Abuse among Female Users: A Study of the Youth in Dhaka City - Mahbub, Fabiha; Rahman, Zia (Social Science Review, 2023)
This paper explores the reasons for female drug abuse in an urban setting. It is concerned with a gender-sensitive approach to one of the burning issues of the 21st century: abusive and non-medical consumption of drugs among the youth. It focuses on social learning theory, control theory, labeling theory, and strain theory to understand and explain why female drug abusers initiate and continue to abuse drugs. This phenomenological research was carried out in three female rehabilitation centers in the Dhaka region. Semi-structured interviews were conducted with twenty research participants: twelve female drug abusers (aged 12-30 years), seven rehabilitation personnel, and an official working with the Department of Narcotics Control, Bangladesh. This study finds some crucial reasons for initiating and continuing drug abuse among young female drug abusers, including traumatic experiences in life, the influence of peers and relatives, curiosity and sensation-seeking, easy access to and availability of unprescribed medicinal drugs, and social stigma. Social Science Review, Vol. 40(1), Jun 2023 Page 21-39